Evaluasi Putaran Balik (U-Turn) Di Ruas Jalan G. Obos Kota Palangka Raya: U-Turn Evaluation In G. Obos Street, Palangka Raya City - Muhammad Khomeini (Media Ilmiah Teknik Sipil, 2023)
Evaluate the U-turn on Jalan G.Obos Palangka Raya, to be precise the U-turn adjacent to the Temanggung Tilung intersection and the Galaxi intersection. The purpose of this research is to determine traffic performance on the U-turn, evaluate the distance between U-turns to intersections according to the geometric U-turn, and provide recommendations for improving road performance for U-turn facilities. Calculating the road performance level using vehicle volume data to get the road capacity. This data was obtained by direct observation/field survey. Road Geometric Data, Traffic Volume, where the data on the volume of vehicles at a specified location in a unit of time. Types of vehicles that can be classified are light vehicles (Kr), heavy vehicles (Kb), two-wheeled motorized vehicles (SM). Traffic performance on U-Turn A and U-Turn B from both sides 1 and 2 has an average value of C, which means: Flow with stable conditions but the speed and movement of vehicles is greatly influenced by higher traffic volumes, for density medium traffic due to increased internal traffic resistance, vehicles have limitations in choosing speed, changing lanes or overtaking. Traffic performance on U-Turn A and U-Turn B from both sides 1 and 2 get an average performance result with a value of C. The distance between U-turn openings is smaller than the standard distance of at least 500 meters, while the distance between U-turn -turn A and U-Turn B 282 meters, to improve U-Turn performance is to move the U-turn to fit the standard minimum distance